Study on the export pattern and export potential of agricultural products from China to RCEP countries—an empirical study based on gravity model - Shi, Lei; Zhang, Shixue; Hashmi, Shabir Mohsin (Frontiers in Sustainable Food Systems, 2025)
Agricultural trade is fundamental to human sustenance and economic development, serving as a critical pillar of the Regional Comprehensive Economic Partnership (RCEP). With the progressive implementation of RCEP, China’s agricultural trade with member countries has exhibited steady growth, underscoring its substantial development potential. Drawing on data from 2009 to 2023, this study systematically examines the export patterns of Chinese agricultural products to RCEP countries. Utilizing the stochastic frontier gravity model, it further explores the key determinants that facilitate or constrain China’s agricultural exports. Moreover, the study assesses export efficiency, untapped potential, and the scope for expansion in China’s agricultural trade with RCEP partners. The findings reveal that New Zealand and Myanmar possess a distinct competitive advantage in agricultural exports. Additionally, factors such as tariff structures, government efficiency, and political stability exert a significant influence on China’s agricultural trade performance. In terms of export potential, China demonstrates considerable opportunities for expanding agricultural exports to Japan, Indonesia, and the Philippines. This study aims to provide theoretical insights and policy recommendations to optimize China’s agricultural trade strategies within the RCEP framework.